2008
DOI: 10.1002/pat.1071
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated polyimide nanocomposites for CO2/CH4 separation

Abstract: The purpose of this project was to synthesize fluorinated polyimide (PI) nanocomposite membranes in order to study the gas permeation rates and selectivity of carbon dioxide and methane. PIs were synthesized from 2,2‐bis(3,4‐anhydrodicarboxyphenyl)hexafluoropropane (6F dianhydride, 6FDA) and 4,4′‐diaminodiphenyl ether (oxydianiline, ODA) into which were incorporated nanoparticulate additives as follows: in situ TiO2, both plain and treated with dodecyl sulfate surfactant, and organo‐clay (Cloisite®‐10 Å) at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…The studies carried out on mixed matrix membranes showed that the type and morphology of the particulate matter included in the membrane matrix might cause a decrease [33,34] or an increase [16,35] in the T g of polymer. In some studies, however, the T g of membrane remained the same with the addition of fillers.…”
Section: Characterizationmentioning
confidence: 99%
“…The studies carried out on mixed matrix membranes showed that the type and morphology of the particulate matter included in the membrane matrix might cause a decrease [33,34] or an increase [16,35] in the T g of polymer. In some studies, however, the T g of membrane remained the same with the addition of fillers.…”
Section: Characterizationmentioning
confidence: 99%
“…An intensive research has been done to modify the physical and chemical properties of polyimides in order to enhance gas permeability and selectivity [17,18]. Polymers containing indan moieties are of great interest for gas separation applications [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This class of materials can exhibit a wide range of physical properties, producing soft or hard materials, or displaying a variety of electric properties from insulators to superconductors. Polymer properties can be modified through copolymerization of monomers with different properties, or by the incorporation of filler materials that are not part of the polymer chain 44–46. Polymer composites can overcome many problems associated with pure polymers, as desirable properties that are not present in the polymer itself can be imparted through proper choice of a filler material.…”
Section: Polymer Compositesmentioning
confidence: 99%